FREE VS. FEE BASED LIBRARY SERVICES: SURVEY OF LIBRARY LEADERS IN PAKISTAN - Mahmood, Khalid; Hameed, Abdul; Haider, Syed Jalaluddin (Malaysian Journal of Library and Information Science, 2005)
This paper reports the findings of a study on the debate of free versus fee based library services in Pakistan. The review of literature revealed that no formal survey on this topic has been carried out before. A questionnaire based survey of selected experts in the field of library and information science from various cities was conducted. Their interviews were also audio-recorded. The library leaders opined on the arguments in favour of and against user fee in libraries. The results show that the respondents are in favour of user fee. However, they advocate for a core service to be offered free of charge as a basic right of the citizens